GeNeDis 2018: geriatrics - Vlamos, Panayiotis (Advances in experimental medicine and biology, 2020)
A hypothesis of circulated microRnas implication in high incidence of atrial fibrillation and other electrocardiographic abnormalities in cancer patients -- Central Line-associated Bloodstream Infections (CLABSI) Incidence and the role of obesity: a prospective, observational study in Greece -- Number of brain states in an N-body dynamical scenario according to the universal Bekenstein entropy bound -- Burden and sleeping disorders of family caregivers of Hemodialysis patients with Chronic Kidney Disease-End Stage. A cross-sectional study -- Quality of life in type 2 diabetes mellitus patients with neuropsychological deficits -- A framework for assessing the impact of information seeking behavior on cancer patients’ long-term prognosis -- Sleeping Disorders and Health Related Quality of Life in Hemodialysis patients with Chronic Renal Disease in Greece -- Subjective Quality of Life, Religiousness and Spiritual Experience in Greek Orthodox Christians: Data from Healthy Aging and Patients with Cardiovascular Disease -- Mini-Mental State Examination: Greek normative data stratified by age and education in a large sample of 925 community-dwelling healthy participants -- The role of the family in the care of Alzheimer patients -- Prevalence of Stroke Cases in Warangal, Telangana Region, India: A Hospital-Based Case Study -- Compliance of Patients with Acute Coronary Syndrome with treatment following their hospitalization from the Cardiac Coronary Unit -- Using a Virtual Reality Serious Game to Assess the Performance of Older Adults with Frailty -- Characteristics and survival rates in ward patients requiring evaluation by Intensivist in Greece.